Indian working class - Mukerjee Radhakamal (Bombay, 1951)
The subject of industrial labour has now come to the forefront in India. There is, however, hardly any topic which is oftener discussed with such indifference to the facts of the situation or to the vital issues involved. Employment in large-scale organised industries is relatively new in this coun try. The industrial worker is in some measure a misfit in his new social environment while the employing class has not developed adequate conventions of fair dealing and conditions of employment. The rapid development of industries and the increase of the landless class which migrates from villages and seeks industrial employment have, indeed, hardly allowed adequate time for either a smooth adjustment of relations bet ween labour and management or the adaptation of the social habits and attitudes of workers to the demands of the indus trial system. The pace of industrialization was greatly acce lerated during the war-time, sharply defining and aggravating the mal-adjustments of the working class which has been up rooted from its fields and villages, but the essential human needs of which are not adequately satisfied in the new urban industrial environment. No sound industrial structure car be built up in the country unless these needs are met, and the hazards and rewards of the industrial system more equi tably distributed among the industry, the community, and the working class. Industrial progress in India also implies her closer trade relations with other countries. Thus peace, safety and prosperity would lie in the approximation of standards of work and of living among different peoples. In fact the con ditions of labour, scale of wages and standards of living of the Indian working class should not be permitted to be far dis parate from those in other industrialized countries of the world, especially when India's war-time production approxi mated in its quality, precision and speed to that reached in those countries. Indian workmen were producing high grade steel and 80 per cent of the articles needed by the Indian army
Keywords: Labour and labouring classes